Mexico / Maria Doulton, Petra Fischer, Eduardo Gleason,... - Doulton, Maria Author
DK Eyewitness Travel Guide: Mexico is your indispensable guide to this beautiful part of the world. The fully updated guide includes unique cutaways, floor plans and reconstructions of the must-see sites, plus street-by-street maps of all the fascinating cities and towns, from Mexico City to the Golf Coast and Yucatan Peninsula. The new-look guide is also packed with photographs and illustrations leading you straight to the best attractions on offer. It provides all the insider tips you need, whether you're hiking in Copper Canyon, salsa dancing in Mexico City, or diving in the Mexican Caribbean.